Crosslinked PVA/SSA proton exchange membranes: correlation between physiochemical properties and free volume determined by positron annihilation spectroscopy. Issue 44 (6th November 2018) - Gomaa, Mahmoud M.; Hugenschmidt, Christoph; Dickmann, Marcel; Abdel-Hady, Esam E.; Mohamed, Hamdy F. M.; Abdel-Hamed, Mohamed O.
Abstract : At low humidity (<30 RH%), water molecules begin to fill the intermolecular spaces in the membrane. At high humidity (80 RH%) the membrane swells; the free volume size increases. Abstract : Two processes for crosslinking polyvinyl alcohol (PVA) with sulfosuccinic acid (SSA) and thermal crosslinking were used to fabricate a proton exchange membrane (PEM). Such PEMs are used in different fields involving fuel cell applications. The crosslinking reaction between PVA and SSA was confirmed using Fourier-transform infrared (FTIR) spectroscopy. The characterization of the prepared membranes, namely, ion exchange capacity (IEC), thermal analyses, water uptake, and ionic conductivity, was carried out. The IEC of the prepared membranes was found to be between 0.084 and 2.086 mmol g −1, resulting in an essential increase in the ionic conductivity. It was observed that the ionic conductivity was in the range of 0.003–0.023 S cm −1, depending on both temperature and SSA content. From the thermogravimetric analysis (TGA) results, it was revealed that the thermal stability of the crosslinked membranes improved. Moreover, water uptake decreased with increasing SSA content. Positron annihilation lifetime spectroscopy (PALS) was used to study the microstructure of the PVA/SSA membranes and their distribution at different ambient temperatures and relative humidity (RH) values. At room temperature, no significant change was observed in the free-volume holes up to 15 wt% SSA; thereafter, the size of the free-volume holes increased with the SSA content. The PALS results show that at different humidity values, the size of the free-volume holes for crosslinked PVA/SSA membranes is lower than those for Nafion membranes, i.e., the gas permeability for the prepared PVA/SSA membranes is less than that for the Nafion membrane. In addition, a strong correlation between the water uptake, ionic conductivity, tensile strength, and free-volume holes was observed.